Alpha-fetoprotein Level Predicts Recurrence After Transplantation in Hepatocellular Carcinoma. Issue 3 (January 2016) - Schraiber, Luciana dos Santos; de Mattos, Angelo Alves; Zanotelli, Maria Lucia; Cantisani, Guido Pio Cracco; Brandão, Ajácio Bandeira de Mello; Marroni, Cludio Augusto; Kiss, Guilhermo; Ernani, Lucas; Marcon, Patrícia dos Santos
Abstract : Abstract: Hepatocellular carcinoma (HCC) is one of the leading causes of liver transplantation. In an attempt to predict their recurrence after liver transplantation, evaluation of tumor number and size, degree of histologic differentiation, and the presence of vascular invasion already have their importance established. In this context, the role of biologic markers such as alpha-fetoprotein (AFP) is still not clear. This retrospective cross-sectional study analyzed the AFP relationship with recurrence of HCC after orthotopic liver transplantation. The current study retrospectively analyzed data from 206 patients with a histopathologic confirmed HCC between 1997 and 2010. The overall survival rates at 1, 3, 5, and 14 years were 78.6%, 65.4%, 60.5%, and 38.7%, respectively. The frequency of recurrence was 15.5%, and recurrence was significantly associated with a lower survival rate ( P  < 0.001). No association was observed between survival and AFP level ( P  = 0.153). A correlation, however, was found between tumor recurrence and AFP level ( P  = 0.002). Univariate analysis of risk factors for recurrence revealed that an AFP level greater than 200 ng/mL, the number of tumors, the degree of cellular differentiation, and the presence of vascular invasion or satellite nodules were associated with relapse. By multivariate analysis, only an AFP level greater than 200 ng/mL remained as a risk factor. Although an elevated AFP level did not correlate with survival in HCC patients undergoing orthotopic liver transplantation, a high AFP level was associated with a 3.32-folds increase in the probability of HCC recurrence.